Pengaruh Penerapan Kurikulum Merdeka Berbasis TIK Terhadap Kemampuan Berpikir Kreatif Siswa pada Mata Pelajaran TIK di MTs Bani Karim Pancalang - Abas, Abdul; Ripai, Ipan (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to determine the impact of implementing a technology-based curriculum on students' creative thinking skills. The independent curriculum is a curriculum that provides freedom and flexibility for schools to develop their curriculum according to the needs and potential of their respective regions. Meanwhile, the use of digital technology in the learning process is expected to enhance students' creativity. The research method that will be used is a quantitative method with a quasi-experimental design featuring pre-test and post-test designs. The research sample consists of eighth-grade students from MTs Bani Karim. The sample was determined using simple random sampling techniques, totaling 46 students, divided into two groups: the experimental group (23 students) and the control group (23 students). The research instrument used is a creative thinking test. Data for the research was collected through pretest and posttest assessments. The data analysis technique employed is the t-test. The research results are expected to show that the implementation of the independent curriculum based on ICT has a positive and significant impact on enhancing students' creative thinking skills. The researchers' findings are expected to contribute to the development of a curriculum and learning that focuses on enhancing students' creativity, as well as serve as a consideration for the government and stakeholders in implementing the independent curriculum in schools